Impact of cardiopulmonary resuscitation duration on functional outcome, level of independence, and survival among patients with in-hospital cardiac arrests: A pilot study - Anandhi D. Amirtharaj; Malarvizhi Suresh; Navaneetha Murugesan; Mony Kurien; Ali H. F. Karnam (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Cardiovascular diseases (CVDs) are the leading cause of cardiac arrest (CA), which are presented as sudden cardiac arrest (SCA) and sudden cardiac death (SCD). To assess the impact of CPR duration on the functional outcome, level of independence, and survival among patients with in-hospital cardiac arrest (IHCA). MATERIAL AND METHODS: This prospective longitudinal pilot study was conducted at a tertiary care hospital in South India. Data were collected using consecutive sampling techniques from nine patients with IHCA, and outcomes were measured using the cerebral performance category (CPC) and Katz level of independence (LOI) during the immediate post-CPR, 30th day, and 90th day. Based on the principles of pilot study design, descriptive statistics was used to analyze the results. Inferential statistics analysis was not applicable based on the sample size of the pilot study. RESULTS: Nine patients were included in this pilot study. The mean and median age of the patients were 48.11 ± 8.66 (46, IQR, 32-67 years) and 77.8% were male patients. The primary medical diagnosis was cardiology and neurology conditions among 44.4% and 22.2% of patients. The mean and median CPR duration was 12.11 ± 4.59 minutes (IQR, 8-15.50) and 44.4% achieved a return of spontaneous circulation (ROSC) with a mean ROSC time of 5.56 ± 7.418. The mean CPC score in the immediate post-CPR period and 30th day was 4 ± 1.732 and 4.56 ± 1.33, with mortality of 66.7% and 33.3% survivors in the immediate post-CPR period. While the mean LOI score among the survivors during the immediate post-CPR and 30th day was zero and four. which highlights the complete dependency of patients during the immediate post-CPR with significant improvement by the 30th day and unchanged until the 90th day. CONCLUSIONS: The overall mortality and survival were 88.8% and 11.1%, respectively, by the 90th day. The pilot study is feasible at the end of the study. However, due to the difficulty in obtaining CA, an additional tertiary hospital was included in the larger study.